The Relationship between Knowledge of the DASH Hypertension Diet and Hypertension Recurrence at the Pademangan Timur Community Health Center, North Jakarta - Thania, Sarah; Wahdini, Rizqa; Rosliany, Nia (LPPM Universitas Dhyana Pura, 2025)
Hypertension is a chronic disease with a continuously increasing prevalence in Indonesia and is a major risk factor for cardiovascular diseases. One way to control hypertension is through a healthy diet, such as the DASH diet (Dietary Approaches to Stop Hypertension). Good knowledge about the hypertension diet is believed to play an important role in reducing the recurrence of high blood pressure. This study aims to determine the relationship between the level of knowledge of the hypertension diet and the recurrence of hypertension in patients at the community health center Pademangan Timur, North Jakarta. The study used a cross-sectional correlational quantitative design with 88 respondents selected through purposive sampling. Data were collected using the DASH diet questionnaire and observation of recurrence over the last 3 months based on medical records, then analyzed using the Chi-Square test and Fisher Exact Test. The results show that the majority of respondents have good to sufficient knowledge (97.5%) and the majority did not experience a relapse (87.5%). There is a significant relationship between knowledge of hypertensive diet and the relapse of hypertension (p = 0.000). It is concluded that good knowledge regarding hypertensive diet can reduce the risk of relapse. Therefore, this study provides evidence that knowledge of the DASH diet plays an important role in preventing hypertension relapse, which impacts the risk of further diseases, and these findings can also be utilized by health workers to strengthen educational programs and healthy diet interventions in promotional and preventive efforts against hypertension.